Painting the CFSP in national colours: Portuguese strategies to help shape the EU's external relations. (1st June 2015) - Robinson, Steven
The agenda-setting power of the rotating Council presidency presented successive Portuguese governments with an opportunity to externalize the country's core foreign-policy priorities onto the European level. As such, Portugal's presidencies of the Council of the European Union have been particularly instrumental in formalizing relations between the EU and the Lusophone world. The first and second EU–Africa summits, the first EU–Brazil summit, the signing of a memorandum of understanding between the Commission and the Executive Secretariat of the Community of Portuguese-speaking countries (CPLP), and the closer association of Cape Verde to the EU, all occurred while Portugal held the rotating Council presidency. This article discusses the strategies, challenges and successes of the three Portuguese presidencies (1992, 2000 and 2007) in shaping the EU's Common Foreign and Security Policy (CFSP). It also explores the options available to Portugal in the post-Lisbon era, where the rotating Council presidency's agenda-setting powers are considerably reduced with regard to CFSP matters. Both prior to and since the Treaty of Lisbon coming into force, Portugal's strategy has been to stress its historic links to Africa and Brazil, as these relations constitute Portugal's contribution to building the CFSP, furthering its core national foreign-policy priorities by putting its position in the Lusophone world at the disposal of the European Union's external action.